Equine corneal stromal abscesses: An evolution in the understanding of pathogenesis and treatment during the past 30 years. (24th August 2012) - Henriksen, M. D. L.; Andersen, P. H.; Plummer, C. E.; Mangan, B.; Brooks, D. E.
Summary The last 30 years have seen many changes in the understanding of the pathogenesis and treatment of equine corneal stromal abscesses (SAs). Stromal abscesses were previously considered an eye problem related to corneal bacterial infection, equine recurrent uveitis, corneal microtrauma and corneal foreign bodies in horses. They were more commonly diagnosed in horses living in subtropical climatic areas of the world. Therapeutic recommendations to treat equine SAs were historically nearly always a medical approach directed at bacteria and the often associated severe iridocyclitis. Today the pathogenesis of most equine SAs appears to be more often related to fungal inoculation of the anterior corneal stroma followed by posterior migration of the fungi deeper into the corneal stroma. There is also now an increased incidence of diagnosis of corneal SAs in horses living in more temperate climates. Medical and surgical treatments are now directed towards elimination of fungal and bacterial infections, reduction and replacement of diseased corneal stroma, and suppression of iridocyclitis. If the abscess and anterior uveitis do not respond satisfactorily to medical therapy, full thickness or split thickness lamellar keratectomy to remove the fungal hyphae and diseased stroma, followed by transplantation of healthy corneal allografts has a high rate of success in speeding healing and preserving sight. This paradigm shift in the ability to diagnose and institute therapy for corneal SAs in horses has evolved over the last 30 years, and is the focus of this paper.